Determinants of funding success in securities crowdfunding: Evidence from equity and sukuk offerings on Indonesia’s Bizhare Platform - Harahap, Khairunnisa; Siregar, Saparuddin; Nurlaila, Nurlaila (Journal of Islamic Economics Lariba, 2026)
IntroductionSecurities Crowdfunding has emerged as an important alternative financing mechanism for Micro, Small, and Medium Enterprises that face difficulties accessing traditional financial institutions. Despite its rapid growth, fundraising outcomes remain highly uneven because investors must make decisions under conditions of information asymmetry. In Indonesia, the coexistence of equity and sukuk offerings within a regulated Securities Crowdfunding ecosystem provides a unique context for examining how issuer and campaign signals influence funding success.ObjectivesThis study investigates the determinants of funding success in Securities Crowdfunding by examining the effects of fundraising experience, business age, fundraising duration, average investment per investor, share price per share, and funding target. The study also explores the role of signaling mechanisms in reducing information asymmetry and enhancing investor confidence.MethodThis study employs a quantitative explanatory approach using cross-sectional data from completed fundraising campaigns listed on Bizhare, one of Indonesia’s licensed Securities Crowdfunding platforms. A purposive sampling technique was applied to select 70 completed campaigns that met predefined criteria. Multiple linear regression analysis was used to examine the effects of issuer and campaign characteristics on funding success.ResultsThe results indicate that fundraising experience, business age, average investment per investor, share price per share, and funding target positively and significantly affect funding success. Funding target emerges as the strongest predictor, followed by share price and average investment per investor. In contrast, fundraising duration does not have a significant effect. The model explains approximately 78 percent of the variation in funding success. In addition, all sukuk campaigns in the sample successfully reached their fundraising targets, suggesting the importance of governance, transparency, and credibility signals in Sharia-compliant fundraising environments.ImplicationsThe findings demonstrate that investors rely on multiple signals to evaluate campaign quality and reduce uncertainty in digital fundraising markets. Issuers should emphasize credible disclosures, realistic funding targets, transparent pricing, and evidence of organizational capability. Regulators and platform operators can strengthen market efficiency by improving disclosure standards and investor information quality.Originality/NoveltyThis study extends signaling theory to the Securities Crowdfunding context by conceptualizing funding target as a strategic signal rather than merely a fundraising threshold. It also contributes to the emerging literature on Islamic fintech by providing evidence from a crowdfunding market where equity and sukuk instruments coexist within the same regulatory framework.